English-Indonesian Translation in a Selected Chapter of Ferreira’s Critical Theory: Evaluating the Google Translate Output - Fuad Abdullah; Bahren Umar Siregar; Vera Nurlia; Muhammad Guruh Nuary (Journal of English Language Studies, 2024)
In this digital era, translation has undergone a radical paradigmatic shift from traditional to automated practices in terms of technological, pedagogical, empirical and economic perspectives, such as the emergence of Machine Translation (MT). Unfortunately, scrutiny accentuating the evaluation of GT output in the English-Indonesian translation setting remains under-researched. Hence, this study aimed at poring over how the English-Indonesian translation in a selected chapter of Ferreira’s critical theory was represented from the GT output. The corpus of this study was a selected chapter of a book entitled International Relations Theory edited by Stephen McGlinchey, Rosie Walters and Christian Scheinpflug (McGlinchey, et. al., 2017), namely chapter 6 in part 1 Critical Theory (Marcos Farias Ferreira) (Ferreira, 2017). The corpus was collected through document analysis and analyzed with Baker’s translation equivalence framework (Baker, 2018) and thematic analysis (TA) (Braun & Clarke, 2006). The findings unveiled that GT output represented English-Indonesian translation in five prominent themes, viz. inappropriate word level equivalence, grammatical equivalence and lexical cohesion in the English-Indonesian translated text, decontextualized pragmatic equivalence in Indonesian as the target language, syntactically disordered English-Indonesian translated words, literally translated Indonesian as the target language, and accepted equivalence of English-Indonesian translation. Pedagogically, this study suggests that a combination strategy of GT-based translation and human translation can be a breakthrough to reach the translation quality, namely accuracy, naturalness and readability.